2006
DOI: 10.1002/adma.200500988
|View full text |Cite
|
Sign up to set email alerts
|

Spatially Confined Corner Defects Induce Chemical Functionality of TiO2 Nanorods

Abstract: The appeal of nanoscience and the allure of nanotechnology have been fostered by the promise of unique properties originating from structural features on the nanoscale. Many literature examples exist in which exceptional electronic, optical, chemical, and biological activities stem from nanoscale materials. [1][2][3][4][5][6][7] The ubiquitous attribute of these examples is their convergence from a "bottom-up" design strategy into pioneering discoveries and devices. In an effort towards the production of funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 26 publications
2
53
1
Order By: Relevance
“…We have found that surface modification of TiO 2 nanoparticles with enediol ligands leads to the bidentate chelation of surface undercoordinated Ti atoms. The forces that are involved in binding the ligands are large enough to induce structural deformation and heal surface defect sites to bulk-like octahedral geometry [18]. As a result of this strong interaction between nanoparticle surface atoms and organic ligands, the surface trapping sites are removed [19] and highly delocalized bands of metal oxide nanoparticles are electronically coupled to organic linkers, making the optical properties of metal oxide nanoparticles tunable throughout the entire visible and near IR region [20].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…We have found that surface modification of TiO 2 nanoparticles with enediol ligands leads to the bidentate chelation of surface undercoordinated Ti atoms. The forces that are involved in binding the ligands are large enough to induce structural deformation and heal surface defect sites to bulk-like octahedral geometry [18]. As a result of this strong interaction between nanoparticle surface atoms and organic ligands, the surface trapping sites are removed [19] and highly delocalized bands of metal oxide nanoparticles are electronically coupled to organic linkers, making the optical properties of metal oxide nanoparticles tunable throughout the entire visible and near IR region [20].…”
Section: Introductionmentioning
confidence: 98%
“…The main drawback for using TiO 2 itself for biological applications is that it absorbs light energy in the UV part of the spectrum. It has been found that surface atoms of anatase TiO 2 are undercoordinated [17,18] and provide an opportunity for alternating the effective band gap of nanoparticles. We have found that surface modification of TiO 2 nanoparticles with enediol ligands leads to the bidentate chelation of surface undercoordinated Ti atoms.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, phagocytosis is the preferred mechanism of entry for the immune cell, whereas, (i) clathrin-mediated endocytosis; (ii) caveolin-mediated endocytosis; (iii) macropinocytosis; and (iv) the clathrin/caveolin-independent pathway are possible for endocyctic pathways. Additionally, passive uptake is a possible mechanism for cellular entry (Tanaka et al 2009;Rabatic et al 2006;Mosesson et al 2008;Johannes and Lamaze 2002). As previously described, multi-functionality and tissue specificity are the hallmark features for developing a hybrid system.…”
Section: Hybrid Nanomaterialsmentioning
confidence: 93%
“…Nanoscale TiO 2 has a surface reactivity that fosters its interactions with biological molecules, such as phosphorylated proteins and peptides [97], as well as some non-specific binding with DNA [25]. Nano-anatase TiO 2 , which is smaller than 20 nm, has surface corner defects that alter the size of the crystal cell [143] ( Table 2). The surface energy of TiO 2 nanoparticles is an important parameter in polymer/filler interaction.…”
Section: Titanium Dioxide (Tio 2 )mentioning
confidence: 99%